A broadly sampled 3-loci plastid phylogeny of Atraphaxis (Polygoneae, Polygonoideae, Polygonaceae) reveals new taxa: I. Atraphaxis kamelinii spec. nov. from Mongolia - Yurtseva, Olga V.; Kuznetsova, Oxana I.; Mavrodiev, Evgeny V. (Phytotaxa, 2016)
Maximum Likelihood (ML) and Bayesian analyses (BI) applied for 3-plastid loci (cpDNA trnL(UAA) intron, trnL–trnF IGS, and rpl32–trnL(UAG) IGS regions) / 65 tips matrix resulted in preliminary phylogenetic reconstruction of the genus Atraphaxis. In combination with the morphological data the obtained phylogeny appears sufficient for recognition of challenging taxonomic entities. We found that a collection of Atraphaxis from the Dzungarian Gobi, which appears to be phylogenetically related to A. pungens, is morphologically different from the latter by the predominantly dimerous perianth and gynoecium, shorter outer perianth segments, and the absence of the spiny shoots. It also differs from all other species of Atraphaxis that occur in Mongolia and neighboring countries. As a result, we described the novel endemic species Atraphaxis kamelinii O.V.Yurtseva sp. nov. More investigations are necessary to fully understand the origin of the newly described species.